Desmovilización y convivencia local: el punto de vista de las comunidades receptoras (2008)
This article presents some results of the research "Shelters for Demobilized: Meanings of convivence and interactions, constructed by organized groups of receptive communities". This research proposed to understand the meanings that the organized groups of receptive community have constructed about the inhabitants of the shelters and the relationship between the arrival of the demobilized ones and the local convivence. We had an intentional sample of eight groups, four of each of two localities of Bogotá. For the analysis we used the method of discourse analysis and the information was gathered from group discussions. This article presents only one of the categories used in the study, that is, convivence. The results show that the receptive community identifies an important alteration in the convivence since the arrival of the demobilized ones, both in the cultural environment and in the structural conditions.